Determinants of Future Stock Returns in the Financial Industry - Judith Judith; Temy Setiawan (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyse the moderating role of corporate governance. fintech adoption and good on the relationship between profitability and stock returns. The motivation of this study is to examine profitability on future stock returns. This quantitative research method used thirty-seven (37) banking companies listed on the Indonesia Stock Exchange in the period 2020 - 2023, which were tested with the SmartPLS 4 program. The implications of this study are expected to provide benefits for investors, banking companies, regulators, academics, and the economy as a whole. This study found that profitability has a positive effect on future stock returns. Meanwhile, GCG is unable to moderate the relationship between profitability and future stock returns; in addition, fintech adoption is unable to moderate the relationship between profitability and future stock returns.